Implementasi Aplikasi Enterprise Resource Planning Odoo 16.0 dengan Metodologi Waterfall di PT. M - Herdianto, Muhammad Fauzan; Widodo, Suryarini (Dinasti Research, 2025)
PT. M is a manufacturing company in the automotive sector that produces motor vehicle components. PT. Arkana Solusi Digital is a company that implements Enterprise Resource Planning (ERP) software at PT. M with its product is Odoo software. One of the main problems in running the manufacturing sector is industrial control and management such as receiving, data collection, shipping and storage of goods or raw materials for the production process. Problems at PT. M is still using the manual method with Microsoft Excel software. Implementation of Odoo version 16 at PT. M aims for company development steps in increasing the effectiveness of production management. The implementation of Odoo version 16 uses the inventory, manufacturing and purchase modules. The implementation process uses the waterfall methodology which consists of project preparation, development, completion and implementation support assistance. Testing was carried out with System Integration Testing (SIT) by PT. Arkana Digital Solutions and User Acceptance Testing (UAT) involving a team from PT. M as a client. The results of the tests which include a description of the process of planning, purchasing, receiving, production to delivery with Odoo version 16 have been running well in accordance with the wishes and needs of the production process at PT. M.